From Australopithecus to cyborgs. Are we facing the end of human evolution? - Aznar, Justo; Burguete, Enrique (Acta Bioethica, 2020)
Social implementation of post-humanism could affect the biological evolution of living beings and especially that of humans. This paper addresses the issue from the biological and anthropological-philosophical perspectives. From the biological perspective, reference is made first to the evolution of hominids until the emergence of Homo sapiens, and secondly, to the theories of evolution with special reference to their scientific foundation and the theory of extended heredity. In the anthropological-philosophical part, the paradigm is presented according to which human consciousness, in its emancipatory zeal against biological nature, must “appropriate” the roots of its physis to transcend the human and move towards a more “perfect” entity; we also assess the theory that refers this will to the awakening of the cosmic consciousness in our conscious matter. Finally, it assesses whether this post-humanist emancipatory paradigm implies true evolution or, instead, an involution to the primitive state of nature.